Dysertacje poświęcone tematyce polskiej, powstałe na Wydziale Filozoficznym Uniwersytetu Wiedeńskiego w latach 1872-1937 - Wiśniewska, Aleksandra (My University, 2010)
Przedmiot niniejszego artykułu stanowią dysertacje poświęcone Polsce, jej historii i kulturze, powstające na Wydziale Filozoficznym Uniwersytetu Wiedeńskiego w ramach dyscyplin humanistycznych w okresie 1872-1937. Dotychczasowe publikacje na ten temat dotyczą przede wszystkim Polaków zdobywających stopnie naukowe w Wiedniu, brakuje jednak kompletnej informacji bibliograficznej w tym zakresie. W niniejszym opracowaniu za punkt wyjścia przyjęto kryterium przedmiotowe, pragnąc zebrać dysertacje poświęcone tematyce polskiej, niezależnie od pochodzenia ich autora. Na podstawie spisów dysertacji z tego okresu znaleziono 143 prace, w tym najwięcej z historii (95), ponadto ze slawistyki, z geografii, germanistyki, muzykologii, historii sztuki, filozofii oraz antropologii i etnologii. Większości z przytoczonych prac (z pojedynczymi wyjątkami) nie uwzględnia jak dotąd retrospektywna Bibliografia polska 1901-1939, ani też Bibliografia polska XIX stulecia Karola Estreichera. Na podstawie mało dotychczas przebadanego źródła wiedzy, jakim są własnoręczne curriculum vitae doktorantów, przechowywane wraz z recenzjami rozpraw w wiedeńskim archiwum, przeanalizowano pochodzenie, drogę życiową i przebieg kariery naukowej niektórych mniej znanych autorów rozpraw. Artykuł prezentuje też wybrane sylwetki wiedeńskich profesorów, pod których kierunkiem powstawały prace poświęcone polskiej tematyce. Całość uzupełnia szczegółowy spis 143 dysertacji, w układzie chronologicznym z podziałem na poszczególne dyscypliny, ze wskazaniem możliwości dotarcia do prac obecnych w zbiorach wiedeńskiej Biblioteki Uniwersyteckiej.

The present article discusses the academic dissertations related to Poland, its history and culture, written at the Philosophical Faculty of the University of Vienna within the framework of humanistic disciplines between 1872-1937. The publications on the subject hitherto published address primarily biographies of well-known Poles pursuing their academic career in Vienna, but there is no relevant comprehensive bibliographical information available. The starting point for the present work is the subject criterion, which has resulted in a compilation of dissertations on Polish subjects regardless of the origin of their authors. On the basis of the lists of dissertations from the period in question, 143 relevant works have been found: the majority of the material on historical issues (95), followed by Slavic studies, geography, German studies, musicology, history of art, anthropology and ethnology. The bulk of the discussed works, with a few exceptions, is not included in the retrospective bibliography Bibliografia polska 1901-1939 and Bibliografia polska XIX stulecia by Karol Estreicher. Hand-written CVs submitted by PhD students of the University at the time, constituting the material of interest not addressed so far, provided an enormous source of information for the author. The CVs, along with reviews, are currently held in the Viennese archives. A close scrutiny of the material made it possible to analyse the social background, life and the professional career of some, hitherto lesser known, authors of the dissertations. The article also presents individual profiles of Viennese professors who were research supervisors to dissertations related to Polish subject matters. The article is complemented with a detailed annotated list of the 143 mentioned dissertations given in a chronological order and subdivided into particular disciplines with an indication of their availability in the collections of the university library in Vienna.
Dissertations on Polish subject themes written at the Faculty of Philosophy of Vienna University in the years 1872-1937
Keywords: Dysertacje; PhD dissertations; tematyka polska; Polish studies; Uniwersytet Wiedeński; University of Vienna; XIX wiek; 19th century